Pengaruh Influncer, Hedonic Shopping Motive, Dan Impulse Buying Terhadap Keputusan Pembelian Pada Pengguna Tiktok Shop Di Jabodetabek - Putri Chindy Narawati; Adryan Rachman (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research was conducted because the researcher saw an interest in purchasing on the TikTok Shop platform. This study has a purpose to understand the influence of influencers and hedonic shopping motivation on Impulse Purchases and the influence of Impulse Buying, Influencers and Hedonic Shopping Motivation on Purchasing Decisions at Tiktok Shop in Jabodetabek. This study uses purposive sampling and probability sampling techniques by taking 170 samples of TikTok Shop user respondents in JABODETABEK. Data collection using the G-form tool with a statement questionnaire with 4 levels of linear scale. This study uses PLS-SEM techniques in hypothesis testing and data validity. The conclusion obtained from this study is that hedonic shopping motivation in TikTok Shop users and Influencers used by TikTok Shop can influence user purchases, but TikTok Shop must re-improve strategies to increase impulse purchases in its users.